2016
DOI: 10.1007/10_2016_13
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Biology for Cell-Free Biosynthesis: Fundamentals of Designing Novel In Vitro Multi-Enzyme Reaction Networks

Abstract: Cell-free biosynthesis in the form of in vitro multi-enzyme reaction networks or enzyme cascade reactions emerges as a promising tool to carry out complex catalysis in one-step, one-vessel settings. It combines the advantages of well-established in vitro biocatalysis with the power of multi-step in vivo pathways. Such cascades have been successfully applied to the synthesis of fine and bulk chemicals, monomers and complex polymers of chemical importance, and energy molecules from renewable resources as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 157 publications
0
25
0
Order By: Relevance
“…The results of the prototyping were subsequently validated with in vivo assays. Cell-free metabolic engineering is thus a promising tool to identify the best combination of enzymes that work together [103,104]. Combining CFPS with cell-free metabolic engineering simplifies the manipulation of metabolic pathways and avoids the need for time-intensive engineering of organisms [105,106].…”
Section: Applications Of Cell-free Protein Synthesismentioning
confidence: 99%
“…The results of the prototyping were subsequently validated with in vivo assays. Cell-free metabolic engineering is thus a promising tool to identify the best combination of enzymes that work together [103,104]. Combining CFPS with cell-free metabolic engineering simplifies the manipulation of metabolic pathways and avoids the need for time-intensive engineering of organisms [105,106].…”
Section: Applications Of Cell-free Protein Synthesismentioning
confidence: 99%
“…To circumvent potential problems caused by cellular complexity 28 , in-vitro enzyme cascades have been used as an alternative to whole-cell biocatalysis. Compared with chemical approaches, enzyme cascades enable the production under moderate, environmentally friendly conditions and, most importantly, provide stereo-selectivity for product formation 29,30 . However, although much simpler than intact cells, one-pot enzyme cascades function similar to metabolic pathways and are subject to regulatory properties (e.g., inhibition by pathway intermediates, (co-)substrates and products) and need quantitative tools for analysis.…”
mentioning
confidence: 99%
“…To identify the rate-limiting step(s) and to optimize enzyme cascades, currently mainly combinatorial approaches are used with non-biased combinations of cascade elements and/or reaction conditions (e.g., buffer composition, pH and temperature) [31][32][33] (for reviews, see ref. 30 ). Rational approaches involving computation and modelling have so far rarely been included [34][35][36][37] and the results for computational pathway design are often hampered by missing data for enzyme properties and incomplete information of systems behaviour.…”
mentioning
confidence: 99%
“…This is especially appealing for product formation from cheap and more easily available substrates and might also be considered as an alternative for KDPG synthesis. Nevertheless, enzyme cascades are more complex to understand and to optimize them is much more complicated and time consuming (Morgado et al, 2018) than single enzyme systems as reported here.…”
Section: Discussionmentioning
confidence: 99%